Women, work & calling : step into your place in God's world - Meyer, Joanna, 1974- (Downers Grove, Illinois : IVP Books, 2023)
"Though women now have professional opportunities beyond what previous generations ever imagined, the church's vision for women's work has not grown with us. Joanna Meyer addresses this gap in women's discipleship, providing a theological framework for women's work and influence and offering resources for the challenges of working life"--
Includes bibliographical references.
Keywords: Church work with women; Christian women -- Religious life; Women employees -- Religious life